Neurorobots as a Means Toward Neuroethology and Explainable AI - Chen, Kexin; Hwu, Tiffany; Kashyap, Hirak J.; Krichmar, Jeffrey L.; Stewart, Kenneth; Xing, Jinwei; Zou, Xinyun (Frontiers in Neurorobotics, 2020)
Understanding why deep neural networks and machine learning algorithms act as they do is a difficult endeavor. Neuroscientists are faced with similar problems. One way biologists address this issue is by closely observing behavior while recording neurons or manipulating brain circuits. This has been called neuroethology. In a similar way, neurorobotics can be used to explain how neural network activity leads to behavior. In real world settings, neurorobots have been shown to perform behaviors analogous to animals. Moreover, a neuroroboticist has total control over the network, and by analyzing different neural groups or studying the effect of network perturbations (e.g., simulated lesions), they may be able to explain how the robot’s behavior arises from artificial brain activity. In this paper, we review neurorobot experiments by focusing on how the robot’s behavior leads to a qualitative and quantitative explanation of neural activity, and vice versa, that is, how neural activity leads to behavior. We suggest that using neurorobots as a form of computational neuroethology can be a powerful methodology for understanding neuroscience, as well as for artificial intelligence and machine learning.